Keyword Based Web Filtering Tool For E-Learning Sites - Modi, Sangita S; Jagtap, Sudhir B (International Journal of Computer Sciences and Engineering, 2018)
The internet overwhelms us with huge amount of widely extended, well integrated, rich and dynamic hypertext information. It has deeply influenced our lives and daily routine. Billions of websites contains learning related and unrelated contents. It is very difficult to find and maintain the unrelated urls dataset to stop student from accessing the irrelevant sites in browser. Web content filtering is one of the essential tool which helps to filter out unwanted content. The proposed algorithm used to create strong keyword database of learning sites. This database used along with browser extension to analyze every incoming site and then allows browser to display only learning sites. In this extension natural language processing (NLP) plays an important role to find out and block non learning sites. We have measured the accuracy of the tool using precision and recall.